Pengaruh Persepsi Konsumen pada Strategi Pemasaran Terhadap Keputusan Pembelian dengan Label Halal Sebagai Moderasi: Studi pada Dika Bakery - Habib Adani; Muhammad Sholahuddin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of consumer perception and marketing strategy on purchasing decisions with halal labels as mediating variables on Dika Bakery consumers in Surakarta. The method used is a quantitative approach with a purposive sampling technique, involving 382 female respondents aged 15–29 years who have purchased the product. The research instrument used a closed questionnaire with a four-point Likert scale. Data analysis was carried out using the Structural Equation Modeling Partial Least Squares (SEM-PLS) approach. The results of the study indicate that consumer perception, product quality, price, and promotion have a significant positive effect on halal labels, while distribution does not have a significant effect. In relation to mediation, halal labels are proven to mediate the influence of product quality and price positively and significantly on purchasing decisions, while the influence of consumer perception, promotion, and distribution does not show significance. The novelty of this study lies in the emphasis on the role of halal labels as a mediating factor in purchasing decisions on food products among young consumers, which is still limited in the existing literature. The contribution of this study is to provide new insights for marketing practitioners in designing strategies that utilize halal labels as an attraction to increase purchasing decisions.